PENGEMBANGAN ALAT PRESS BRIKET SERBUK KAYU DENGAN METODE DESIGN FOR MANUFACTURING AND ASSEMBLY (DFMA) - Muhammad Farhan (2021)
Wood grain is waste produced by the wood industry that is still underutilized. Wood industry in Indonesia can be counted a lot until now, therefore the utilization of wood grain must be optimized by utilizing wood grain waste for briquette raw materials. However, the lack of affordable briquette press tools become obstacles for the community and briquette businesses, therefore briquette press tools need to be developed in terms of design using the Design For Manufacturing and Assembly (DFMA) method. DFMA method is able to reduce the number of components, make the design of briquette press tools more complex or efficient and can reduce the cost of materials and production, causing the selling price of briquette press tools to decrease. In this paper the briquette press tool is redesigned from the previous tool using the DFMA method. The purpose of this writing is to make a wood grain briquette press tool that can be reached by the community. The tool uses hydraulic jacks to lift and propel the briquette printing process. The hydraulic jack is moved manually and placed on top of the mold pusher connected to the tool frame which has dimensions of 580 mm x 350 mm x 600 mm and is assisted by a pull spring. From the results of research the DFA index on the new design has an efficiency of 2.2%, production capacity is 15.48 Kg/Hour increased from the previous design and cost of production is Rp.1,193,096 lower than the previous design.